Digital Transformation in Operational Management: A Systematic Review of Current Trends and Practices - Supriadi, Asep; Mulyani, Ana Susi (Penelitian dan Pengembangan Ilmu, 2024)
This research investigates the impact of digital transformation technologies, including artificial intelligence (AI), Internet of Things (IoT), and big data, on operational decision making in the context of operational management. Through a comprehensive literature analysis, this research presents findings from studies that reveal the important role of digital technology in increasing operational efficiency, improving decision making, and facilitating innovation in various industrial sectors. The research findings highlight the importance of understanding the integration of digital technologies with existing operational management practices, as well as the ethical and organizational challenges associated with their use. In addition, this research identifies a number of potential research agendas to develop a deeper understanding of digital transformation in operational management and provide valuable guidance for organizations in facing the challenges and exploiting opportunities in this digital era.